Total THB. Volume 1 - Pope, Paul (23rd St., 2025)
Discover the indie sci-fi epic that broke new ground in graphic novels with Total THB, Volume 1. Mars is a planet divided. In the north, the bohemian Plutonium City teems with music and art. In the south, the people of Velo City are stifled by an oppressive bureaucracy with a tightening grip. And it is in Velo City that we find HR Watson, the sheltered daughter of a wealthy industrialist, and THB, her loyal but mysterious bodyguard who can expand from a tiny rubber ball to a nine-foot-tall humanoid with just a splash of water. To HR, THB is a novelty--a strange new toy of dubious value. But when she finds herself in the crosshairs of her father's enemies, HR will quickly discover the true extent of THB's power. Over thirty years since its debut, the world of THB continues to inspire loyal readership and critical acclaim. Now for the first time, New York Times-bestselling author and Eisner Award-winner Paul Pope's sprawling, self-published vision is gathered in three definitive editions, featuring remastered art and exclusive new material.